PENGARUH LAMA PERENDAMAN KAIN KATUN TERHADAP DAYA WARNA YANG DIHASILKAN EKSTRAK AKAR MENGKUDU (MORINDA CITRIFOLIA) SEBAGAI PEWARNA ALAMI - Sari, Myra Wardati; -, Cengristitama; Sopian, Yogi; Wulandari, Ratna Rizky (UPPM Politeknik TEDC Bandung, 2025)
The textile industry requires innovation in the use of dyeing materials that are not only effective but also environmentally friendly. One potential source of natural dyes is noni root (Morinda citrifolia), which contains anthocyanin and morindone compounds as coloring agents. This study aims to examine the effect of immersion duration on the color strength of cotton fabric dyed with natural dye extracted from noni root (Morinda citrifolia). The dye extraction was carried out using two methods: heating (batch) and maceration with methanol as the solvent. The dyeing process included mordanting, dyeing with varying immersion duration (8, 16, 24, 32, and 40 hours), and fixation. The results showed that longer immersion duration increased amount of dye bound to the fabric in both extraction methods. Color fastness tests produced results categorized as poor (2–3/2.5), fair (3.0), and good (4/4–5/4.5). These findings indicate that natural dye extracted from noni root can be used as an alternative natural dye for textiles, particularly cotton fabric, with sufficient color stability.